Novel topical esmolol hydrochloride improves wound healing in diabetes by inhibiting aldose reductase, generation of advanced glycation end products, and facilitating the migration of fibroblasts - Kulkarni, Sudhir A.; Deshpande, Supreet K.; Rastogi, Ashu (Frontiers in Endocrinology, 2022)
Aims/Objectives Wound healing in people with diabetes is delayed secondary to impaired nitric oxide generation, advanced glycation end products (AGE), and poor migration of epithelial cells. We developed a novel topical esmolol hydrochloride (Galnobax) and assessed its efficacy for wound healing in streptozocin-induced diabetic hairless rat. Methods All experiments were performed at an animal laboratory and tertiary-care research facility. Ex vivo aldose reductase inhibition was assessed from enzymes obtained from a bacterial culture (spectrophotometer), sorbitol content in homogenized red blood cells, and AGE in glucose and bovine serum by fluorometry following the addition of esmolol in varying concentrations. A scratch assay of human fibroblasts, endothelial cells, and keratinocytes was assessed under a high-glucose environment and after esmolol by phase-contrast microscopy. The efficacy evaluation of the topical application of Galnobax (14 and 20%) or vehicle was conducted in streptozotocin-induced diabetic hairless rats, and endogenous nitrite and hydroxyproline from homogenized wound tissue were measured along with pharmacokinetic and dermal toxicity in Hanford miniature swine. Results Esmolol inhibited the formation of sorbitol by 59% in erythrocytes in comparison to glucose-induced sorbitol levels. AGE generation in bovine serum albumin was reduced at 1 mM esmolol concentrations (2.6 ± 1.7) compared with control (p < 0.05) and similar to that of diclofenac (2.5 ± 1.3). Esmolol at 1 and 10 µM enhanced the migration of fibroblasts, epithelial cells, and keratinocytes compared with control. The nitric oxide levels (day 7) were 44 and 112% higher with Galnobax (14%) than those of the diabetic group (p < 0.05) and the vehicle control group (p < 0.05), respectively. The days 7 and 14 hydroxyproline in the wound was higher by 22 and 44% following Galnobax (14%) compared with the diabetic and vehicle control groups. The wound area exhibited better reduction with Galnobax at 14% up to day 10 follow-up compared with the controls. The pharmacokinetic and dermal toxicity in miniature swine suggested no significant adverse event with Galnobax. Conclusions Topical esmolol hydrochloride is a novel, safe, and effective treatment modality that acts through pleotropic mechanisms to hasten wound healing in diabetes.